Related Factors of Anxiety Level in Covid-19 Patient during Self Quarantine - Husna, Putri Halimu; Ratnasari, Nita Yunianti; Marni, Marni (KEMAS: Jurnal Kesehatan Masyarakat, 2022)
Coronavirus disease-19 was a pandemic in the world. One of the efforts to reduce the spread of Covid-19 cases was to self-quarantine. Self-quarantine impacted emotional mental disorders in the form of anxiety. This study aimed to identify factors related to the anxiety of Covid-19 patients who were undergoing self-quarantine. METHODS: This study used a descriptive research design with a cross-sectional study. The population was all confirmed COVID-19 patients who underwent self-quarantine in Wonogiri Regency as many as 70 respondents. Samples used clustered randomized sampling with 40 respondents. The instrument used a sociodemographic questionnaire, and anxiety was measured using Hamilton Rating Scale-Anxiety. Data were analyzed using multiple linear regression. RESULTS: The results showed that the mean age was 33.58 ± 11.08 years. Most participants were women 52.5%, 87.5% of the respondents had high education background, 37.5% were medical workers, 37.5% were private workers,  and 95% of the participants had received information about covid-19. The mean of the time they were self-quarantined was 8.1 ± 4.77 days. 55% of the participants had no anxiety, 15% had mild anxiety, 10% had moderate anxiety, and 20% had severe anxiety. Factors that affect the level of anxiety are age (p-value = 0.047), occupation (p-value = 0.031), education (p-value = 0.035) and length of self-quarantine (0.023). CONCLUSION: The conclusion said that age, occupation, education, and length of self-quarantine have a strong relationship and have a significant effect on anxiety. Social support is needed to reduce the anxiety of COVID-19 patients during self-quarantine.